Penerapan Model Project Based Learning Berbasis Media E-Flashcard dalam Meningkatkan Pemahaman Kosakata Bahasa Indonesia pada Kelas II SDN 1 Mantup - Dhea Nur Savira; Ahmad Ipmawan Kharisma; Humairah (Mataram University, 2026)
Limited vocabulary comprehension among second-grade students at SDN 1 Mantup was caused by the use of less varied teaching models and conventional learning media. This study aimed to improve students' Indonesian vocabulary comprehension through the implementation of the Project Based Learning model supported by E-Flashcard media. This study employed Classroom Action Research (CAR) based on the model of Suharsimi Arikunto, conducted in two cycles involving 15 second-grade students at SDN 1 Mantup. Data were collected through classroom observations of teacher and student activities, vocabulary comprehension tests, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The findings revealed significant improvements in both the learning process and students' vocabulary comprehension. Teacher activity increased from 45% in Cycle I to 83% in Cycle II, while student activity improved from 54% to 76%. Furthermore, students' classical mastery of vocabulary comprehension increased from 40% in Cycle I to 86% in Cycle II, exceeding the predetermined success criterion. These findings indicate that the implementation of the Project Based Learning model supported by E-Flashcard media effectively enhances students' vocabulary comprehension. The study implies that this instructional approach can serve as an innovative alternative for Indonesian language learning in elementary schools by promoting active, engaging, and student-centered learning while improving vocabulary comprehension skills.